Plastic Pollution and Potential Solutions. (September 2018) - Rhodes, Christopher J.
A review is presented of the manufacture and use of different types of plastic, and the effects of pollution by these materials on animal, human and environmental health, insofar as this is known. Since 2004, the world has made as much plastic as it did in the previous half century, and it has been reckoned that the total mass of virgin plastics ever made amounts to 8.3 billion tonnes, mainly derived from natural gas and crude oil, used as chemical feedstocks and fuel sources. Between 1950 and 2015, a total of 6.3 billion tonnes of primary and secondary (recycled) plastic waste was generated, of which around 9% has been recycled, and 12% incinerated, with the remaining 79% either being stored in landfills or having been released directly into the natural environment. In 2015, 407 million tonnes (Mt) of plastic was produced, of which 164 Mt was consumed by packaging (36% of the total). Although quoted values vary, packaging probably accounts for around one third of all plastics used, of which approximately 40% goes to landfill, while 32% escapes the collection system. It has been deduced that around 9 Mt of plastic entered the oceans in 2010, as a result of mismanaged waste, along with up to 0.5 Mt each of microplastics from washing synthetic textiles, and from the abrasion of tyres on road surfaces. However, the amount of plastics actually measured in the oceans represents less than 1% of the (at least) 150 Mt reckoned to have been released into the oceans over time. Plastic accounts for around 10% by mass of municipal waste, but up to 85% of marine debris items – most of which arrive from land-based sources. Geographically, the five heaviest plastic polluters are P.R. China, Indonesia, Philippines, Vietnam and Sri Lanka, which between them contribute 56% of global plastic waste. Larger, primary plastic items can undergo progressive fragmentation to yield a greater number of increasingly smaller 'secondary' microplastic particles, thus increasing the overall surface area of the plastic material, which enhances its ability to absorb, and concentrate, persistent organic pollutants (POPs) such as dichlorodiphenyltrichloroethane (DDT) and polychlorinated biphenyls (PCBs), with the potential to transfer them to the tissues of animals that ingest the microplastic particles, particularly in marine environments. Although fears that such microparticles and their toxins may be passed via food webs to humans are not as yet substantiated, the direct ingestion of microplastics by humans via drinking water is a distinct possibility – since 92% of samples taken in the USA and 72% in Europe showed their presence – although any consequent health effects are as yet unclear. Foodstuffs may also become contaminated by microplastics from the air, although any consequent health effects are also unknown. In regard to such airborne sources, it is noteworthy that small plastic particles have been found in human lung tissue, which might prove an adverse health issue under given circumstances. It is also very striking that microplastics have been detected in mountain soils in Switzerland, which are most likely windborne in origin. Arctic ice core samples too have revealed the presence of microplastics, which were most likely carried on ocean currents from the Pacific garbage patch, and from local pollution from shipping and fishing. Thus, sea ice traps large amounts of microplastics and transports them across the Arctic Ocean, but these particles will be released into the global environment when the ice melts, particularly under the influence of a rising mean global temperature. While there is a growing emphasis toward the substitution of petrochemically derived plastics by bioplastics, controversy has arisen in regard to how biodegradable the latter actually are in the open environment, and they presently only account for 0.5% of the total mass of plastics manufactured globally. Since the majority of bioplastics are made from sugar and starch materials, to expand their use significantly raises the prospect of competition between growing crops to supply food or plastics, similarly to the diversion of food crops for the manufacture of primary biofuels. The use of oxo-plastics, which contain additives that assist the material to degrade, is also a matter of concern, since it is claimed that they merely fragment and add to the environmental burden of microplastics; hence, the European Union has moved to restrict their use. Since 6% of the current global oil (including natural gas liquids, NGLs) production is used to manufacture plastic commodities – predicted to rise to 20% by 2050 – the current approaches for the manufacture and use of plastics (including their end-use) demand immediate revision. More extensive collection and recycling of plastic items at the end of their life, for re-use in new production, to offset the use of virgin plastic, is a critical aspect both for reducing the amount of plastic waste entering the environment, and in improving the efficiency of fossil resource use. This is central to the ideology underpinning the circular economy, which has common elements with permaculture, the latter being a regenerative design system based on 'nature as teacher', which could help optimise the use of resources in town and city environments, while minimising and repurposing 'waste'. Thus, food might be produced more on the local than the global scale, with smaller inputs of fuels (including transportation fuels for importing and distributing food), water and fertilisers, and with a marked reduction in the use of plastic packaging. Such an approach, adopted by billions of individuals, could prove of immense significance in ensuring future food security, and in reducing waste and pollution – of all kinds.